Time series monitoring and analysis of Pakistan’s mangrove using Sentinel-2 data - Raza, Syed Ahmed; Zhang, Li; Zuo, Jian; Chen, Bowei (Frontiers in Environmental Science, 2024)
Sustainable Development Goal-14 (SDG-14) directly demands the protection, conservation, restoration and sustainable management of the global mangrove ecosystem. Assessment of the development Pakistan has made towards the sustainable management of mangrove ecosystems necessitates the remote sensing-based evaluation of national-level mangrove cover. Using Google Earth Engine (GEE) for geoprocessing 12000+ 10-m high-spatial resolution Sentinel-2 time series images (2016-23) and applying Random Forest (RF) classifier, current research provides the latest spatial distribution of mangroves along Pakistan’s coastline and 8-year long temporal changes in it. Additionally, this research provides the first spatiotemporal health assessment of Pakistan’s national mangroves as well. Rational analysis of the results indicated splitting the entire timeline based on two seasons (Jan-Jun and Jul-Dec). Results revealed an overall 1210 km2 (2023) national-level mangroves; a 3.42 km2 average annual increase from 2016 (1186 km2). Mangrove gain/loss assessment based on Land Use Land Cover (LULC) transition matrix illustrated 223 km2 gain whereas 199 km2 loss; a 24 km2 net gain. 20.28% and 7.91% declines were found in maximum- and mean-NDVI (2016-23), depicting the deteriorating mangrove health conditions. Likewise, significant Sen’s slope analysis (p<0.05) indicated that 88.8% of all the mangrove-NDVI pixels exhibited an overall decrease whereas 11.2% pixels showing an overall increase (2016-23). It was concluded that despite showing a growth in the extent, the Pakistan’s mangroves have shown a decline in health, primarily due to deforestation for urban operations and sea-level rise, still making them vulnerable and potentially leading to disrupted ecosystem including carbon release in atmosphere. This study will assist in the formulation of mangroves conservation and management strategies whereas future research can explore the potentials of Land Surface Temperature (LST) and evapotranspiration in combination to NDVI for an in-depth analysis of health status of mangroves.